The Here and Now - Brashares, Ann (New York : Delacorte Press, an imprint of Random House Children's Books, 2014)
Seventeen-year-old Prenna, an immigrant who moved to New York when she was twelve, came from another time and she and the other travelers must follow strict rules to avoid destroying the new life they have worked so hard to get, as well as the one person Prenna is desperate to protect.
Keywords: Interpersonal relations -- Juvenile fiction; Refugees -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Community life -- Juvenile fiction -- New York (State); Time travel -- Juvenile fiction; Interpersonal relations -- Fiction; Refugees -- Fiction; High schools -- Fiction; Schools -- Fiction; Community life -- Fiction -- New York (State); Time travel -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction